Teaching students in graphic subjects - Yessekeshova , Марал; Tuleuova , Гульмаржан (Рroblems of engineering and professional education, 2024)
The article considers the change of attitude to teaching descriptive geometry and drawing. Due to underdeveloped spatial thinking, many students have difficulties in studying graphic disciplines. The decrease in the quality of students' graphic education leads to the deterioration of their abilities to logical spatial thinking and, as a consequence, to the decrease in the quality of learning engineering disciplines. By not noticing or missing something while watching animation, learners passively assimilate information. This eliminates the need to visualize the mental interaction of machine parts during a work cycle, such as a static sketch or drawing.